ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN NEONATAL DI PUSKESMAS KAMPUNG BAQA SAMARINDA TAHUN 2018 - Siti Salasiah (Universitas Widya Gama Mahakam Samarinda, 2018)
At the age of less than 28 days newborns are very span to death, so at this time need to be aware of some signs and dangers in the newborn. One of the efforts undertaken to reduce the infant mortality rate is neonatal visits conducted in health services. This study aims to determine several factors related to Neonatal Visits (KN) in the work area of Puskesmas Kampung Baqa in 2018. This study uses Analytical Survey, with cross sectional approach. Respondents of this study were all mothers who had babies aged 0-28 days as many as 87 respondents with sampling techniques using puposive sampling. Data analysis performed was univariate and bivariate with Chi-Square test. The results of this study found that all the variables studied were associated with neonatal visits in the work area of Puskesmas Kampung Baqa in 2018, namely knowledge (p value 0,000), attitude (p value 0,000) and family support (p value 0,006). The conclusion in this research is that knowledge, attitude, and support of mother's family can influence visit of neonatal mother to conduct Neonatal Visit (KN). Therefore, it is necessary to be counseled about the importance of conducting neonatal visits to the public by health workers intensively so that the knowledge of the community especially the mothers who have babies 0-28 days to increase. Keywords : Visit Neonatal, Knowledge, Attitude, Family SupportBibliograpy : 25 (1991-2017).